2012
DOI: 10.1021/es204028v
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Biotransformation of Perfluorooctane Sulfonamide in Sprague–Dawley Rats

Abstract: Great variability exists in perfluorooctane sulfonate (PFOS) isomer patterns in human and wildlife samples, including unexpectedly high percentages (e.g., >40%) of branched isomers in human sera. Previous in vitro tests showed that branched PFOS-precursors were biotransformed faster than the corresponding linear isomer. Thus, high percentages of branched PFOS may be a biomarker of PFOS-precursor exposure in humans. We evaluated this hypothesis by examining the isomer-specific fate of perfluorooctane sulfonamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 43 publications
6
60
0
Order By: Relevance
“…1), is in line with the trends observed in food. This trend could also (partly) be explained by shorter disappearance half-lives of branched isomers compared to the linear isomer (Table 1), which could be the result of faster biotransformation of branched isomers to branched PFOS relative to the linear isomer (Benskin et al, 2009;Ross et al, 2012). Faster urinary elimination of linear precursors relative to branched precursors, as was observed in humans (Zhang et al, 2013a), would, on the other hand, result in increasing relative importance of branched precursor isomers over time.…”
Section: Pfaa and Precursor Isomers In Swedish Serum Samplesmentioning
confidence: 90%
“…1), is in line with the trends observed in food. This trend could also (partly) be explained by shorter disappearance half-lives of branched isomers compared to the linear isomer (Table 1), which could be the result of faster biotransformation of branched isomers to branched PFOS relative to the linear isomer (Benskin et al, 2009;Ross et al, 2012). Faster urinary elimination of linear precursors relative to branched precursors, as was observed in humans (Zhang et al, 2013a), would, on the other hand, result in increasing relative importance of branched precursor isomers over time.…”
Section: Pfaa and Precursor Isomers In Swedish Serum Samplesmentioning
confidence: 90%
“…Current evidence to support this hypothesis is not clear-cut however (Ross et al, 2012). While excretion in rats of branched chain PFOSAs exceeded that of the linear isomer; a corresponding increase in the relative abundance of the sum of branched chain PFOS isomers was not observed in the same animals.…”
Section: Isomer Profilesmentioning
confidence: 91%
“…More detailed analysis of the relative abundance of individual branched chain isomers in this study suggests a more complex situation. While the relative abundance in the studied rats of one branched isomer (5 m-PFOS), increased relative to its abundance in a commercial PFOS mixture; that of another (1 m-PFOS) decreased (Ross et al, 2012). This may point to a need to monitor relative abundances of individual branched chain isomers rather than the sum of all such isomers, to provide more conclusive insights into the relative contribution of precursor exposure.…”
Section: Isomer Profilesmentioning
confidence: 96%
See 1 more Smart Citation
“…Commercially relevant batches of PreFOS were also~30% branched (Korkowski and Kestner, 1999;Reagen et al, 2008), and studies have shown the preferential excretion of linear PreFOS (i.e. perfluorooctanesulfonamide (FOSA)) compared to branched PreFOS through urine in rodents (Ross et al, 2012) and in humans (Zhang et al, 2013a), resulting in preferential retention of branched FOSA isomers that can then be biotransformed to branched PFOS. Moreover, branched PreFOS isomers are metabolized faster than linear PreFOS in vitro by human liver microsomes (Benskin et al, 2009b) and in vivo in rats (Benskin et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%